Kelp-Associated Microbes Facilitate Spatial Subsidy in a Detrital-Based Food Web in a Shoreline Ecosystem - Singh, Charu Lata; Huggett, Megan J.; Lavery, Paul S.; Säwström, Christin; Hyndes, Glenn A. (Frontiers in Marine Science, 2021)
Microbes are ubiquitous but our knowledge of their effects on consumers is limited in benthic marine systems. Shorelines often form hotspots of microbial and detritivore activity due to the large amounts of detrital macrophytes that are exported from other coastal ecosystems, such as kelp forests, and accumulate in these systems. Shoreline ecosystems therefore provide a useful model system to examine microbial-detritivore interactions. We experimentally test whether bacteria in the biofilm of kelp provide a bottom-up influence on growth and reproductive output of detritivores in shorelines where detrital kelp accumulates, by manipulating the bacterial abundances on kelp (Ecklonia radiata). The growth rates for both male and female amphipods (Allorchestes compressa) were greater in treatments containing bacteria than those in which bacteria were reduced through antibiotic treatment, and this effect was greater for males offered aged kelp. The proportions of ovigerous females were greater when reared on kelp with intact bacteria, indicating a more rapid reproductive development in the presence of more bacteria. Bacterial abundance had little to no influence on nutrient content and palatability of kelp, based on tissue toughness, nitrogen and carbon content and C:N ratio. Thus, the most likely pathway for a microbial effect on detritivores was through feeding on kelp-associated bacteria. Regardless of the pathway, kelp-associated microbes have a strong influence on the fitness of a highly abundant detritivore that feeds preferentially on E. radiata in shoreline systems, and therefore form a hidden trophic step in this “brown” food web and a hotspot of secondary production.